The Type III Secretion System (T3SS) of Escherichia Coli Promotes Atherosclerosis in Type 2 Diabetes Mellitus - Yao‐Yuan Zhang; Song‐Tao Chen; Gang Chen; Le Zhou; Guo‐Liang Zhou; Xin‐Yuan Yu; Long Yuan; Wei‐Qian Deng; Zhen‐Bo Wang; Jing Li; Yi‐Fu Tu; Da‐Wei Zhang; et al. (Advanced Science)
Abstract Large‐scale studies indicate a strong relationship between the gut microbiome, type 2 diabetes mellitus (T2DM), and atherosclerotic cardiovascular disease (ASCVD). Here, a higher abundance of the type III secretion system (T3SS) virulence factors of Enterobacteriaceae/Escherichia‐Shigella in patients with T2DM‐related‐ASCVD, which correlates with their atherosclerotic stenosis is reported. Overexpression of T3SS via Citrobacter rodentium (CR) infection in Apoe‐/‐ T2DM mice exacerbated atherosclerotic lesion formation and increased gut permeability. Non‐targeted metabolomic and proteomic analysis of mouse serum showed that T3SS caused abnormal glycerophospholipid metabolism in mice. Proteomics, RNA sequencing, and functional analyses showed that T3SS induced ferroptosis in intestinal epithelial cells, partly due to increased expression of ferritin heavy chains (FTH1). This findings first demonstrated that T3SS increases ferroptosis in intestinal epithelial cells, via disrupting the intestinal barrier and upregulation of phosphatidylcholine, thereby exacerbating T2DM‐related ASCVD.